Performance in "Noir et Blanc": Le Chevalier de Saint-Georges in Theatre - Mounsef, Donia (Alternative francophone, 2025)
If we consider Le Chevalier de Saint-Georges (also known as Joseph Boulogne or Boullongne 1745-1799) – a decorated military hero whose swordsmanship, fighting and athletic acumen were unparalleled, a contemporary of Mozart whose musical, composing and conducting talent remained unsurpassed – it comes as a surprise that his character was never developed for the theatre until the 1840s, four decades after his death. This, even though the French stage frequently celebrated revolutionary and heroic characters, especially after the revolutionary decree of 1791 that liberated theatres from censorship. The first play to be written about Le Chevalier in France: Le Chevalier de Saint-Georges : comédie mêlée de chant en trois actes by Roger de Beauvoir (1807-1866) and M. Mélesville (1787-1865) made waves when it premiered at the Théâtre des Variétés in Paris in February 1840. Le Chevalier de Saint-Georges had all the characteristics to make a spectacular theatrical character with all the archetypal contradictions of the Romantic hero. Some of the reasons for this delay may be obvious: playing a black hero on the post-revolutionary French stage is not a simple feat and comes with a slew of complications related to race and representation, as this article discusses.